Revolução copernicana-galileana : aspectos histórcos e epistemológicos - Soares Junior, Jarbas Antônio (2023)
The Galilean Copernican revolution involved more than the adoption of a new astronomical configuration based on the movement of the Earth and the immobility and centrality of the Sun. With his new astronomy, Copernicus provided a significant change in the way we perceive the world. Before, reason, like the Sun, orbited the world of appearances and sought to illuminate it, giving it a rational meaning. With Copernicanism, reason was kept immobile and the world of appearances began to orbit it. This dissertation aims to show that this inversion represented a greater action by the subject of knowledge, who now no longer passively accepts the reality of what he saw by actively reinterpreting the data of sensitive experience, and this in the light of mathematical rationality. This led to a transformation of scientific experience, which was no longer guided by a naive phenomenology, that is, by a direct perception of sensitive reality and began to be actively conditioned by two principles, na epistemological one that acts on the subject in the act of observation, and another mechanical one, which confers the necessary physical rationality to the sensitive experience in such a way that both principles the earthly observer’s sensitive experience compatible With a moving Earth. to sensitive experience. Both principles depend on a new conception of movement, which takes into account the state and position of the observer and the thing observed. Therefore, we will analyze from an epistemological perspective the two main works that led to the modern scientific revolution: De Revolutionibus by Nicolaus Copernicus and the Dialogue on Two Maximum Systems of the Copernican and Ptolemaic world by Galileo Galilei.